2023
DOI: 10.21037/tcr-23-909
|View full text |Cite
|
Sign up to set email alerts
|

The transcription activity of OTX2 on p16 expression is significantly blocked by methylation of CpG shore in non-promoter of lung cancer cell lines

Honghao Peng,
Wenfan Fu,
Chong Chang
et al.

Abstract: Background The aberrant expression of the classical tumor suppressor gene p16 is a frequent event in lung cancer mainly due to the hypermethylation of its 5’-cytosine-phosphate-guanine-3’ island (Cgi). However, whether methylation happens in other regions and how p16 expression and function are affected are largely unknown. Methods Clustered Regularly Interspaced Short Palindromic Repeats/dCas9 (CRISPR/dCas9) technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It functions by inhibiting the growth of tumor-killing cells (Muss et al, 2020). Several studies have indicated that hypermethylation of the p16 gene is strongly associated with poor prognosis in patients diagnosed with colorectal cancer (Karam et al, 2019), liver cancer (Wong et al, 1999), and lung cancer (Peng et al, 2023). Another gene involved in cancer development is glutathione S-transferase 1 (GSTP1).…”
Section: Line-1mentioning
confidence: 99%
“…It functions by inhibiting the growth of tumor-killing cells (Muss et al, 2020). Several studies have indicated that hypermethylation of the p16 gene is strongly associated with poor prognosis in patients diagnosed with colorectal cancer (Karam et al, 2019), liver cancer (Wong et al, 1999), and lung cancer (Peng et al, 2023). Another gene involved in cancer development is glutathione S-transferase 1 (GSTP1).…”
Section: Line-1mentioning
confidence: 99%